(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Micro-encapsulated pigments were formulated into biodegradable printing pastes and their properties were analyzed. The pigment was used as the core material and polylactic-based biodegradable thickener was used as the wall-former. Cotton/polyester blend fabric was printed with micro-encapsulated pigment using screen-printing technique without dispersing agents, penetrating agents, leveling agents or other auxiliaries. Micro-encapsulated pigment has been characterized in terms of average particle size and size distribution, morphological structure and elemental composition using scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDX). The variations in viscosity and paste stability were observed upon storing over 7 days at ambient temperature. For permanence, the micro-encapsulation process afforded better colorfastness properties against light, washing, rubbing, and perspiration.